(3fUa GdYjT (B((3CQLhRI(B)s - (3GHf GdhMjO , eMeO Hf TQja Hf jhSa, TQa GdOjf,J (B711 (3g` s
(3ChdgG (B:s
(3GdHGH GdChd(B: (3hgh jTJed Ydi ebOeI hLedI(B: (3GdebOeI(B: (3GdMeO ddg GdYdqj GdCcHQ oeQTOfG HMce aj GdRHQ s
(3BNQgG (B:s
(3Ke UdGI Gddg hGdSdGe Ydi fHj Ojfg GdESdGe hBdg Ydi OhGe GdOgQ s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdChds
(3bOegG ddedc GdpCTQa Ndjd Hf bdGhhf HChdgG CfgG ddNRGfI GdYGdjI GdehdhjI GdSjOjI GdRjfHjI hUaMI GdYfhGf eRjfI HGdRNGQa hGdCdhGfs
(3HChdgG hBNQgG Jedc deMeO Hf CHj HcQ Hf eMeO GddGPbj GdeJWHH GdTgjQ HGdhgL cJHg aj WQGHdSs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs